ANALYSIS OF SANITATION IN PUBLIC PLACES AND CREATING A CLEAN AND HEALTHY ENVIRONMENT - Permatasari, Bina Rachma; Hartono, Budi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Cleanliness is a preventive effort that focuses on the healthy for human environmentally. Goal of environmental health work is to create a healthy and high-quality environment at the physical, chemical, biological and social levels that enables everyone to achieved higher possiblity level for health. The purpose of studying these problems is to better understand and be able to implement solutions to sanitation problems in these public places. By paying attention to the causes of sanitation problems in the public environment, the authors can properly apply the causes and effects so that problems regarding sanitation in public places in Indonesia can be resolved better and become cleaning and healthy environmentally. By improving the facilities for providing trash bins in every corner of the environment, increasingly public aware of the importances of environmentally health is obtained from socialization and several other supporting activities that can increase social awareness of the important of environmentally sanitation.